Development of a range-extended electric vehicle powertrain for an integrated energy systems research printed utility vehicle. (1st April 2017) - Chambon, Paul; Curran, Scott; Huff, Shean; Love, Lonnie; Post, Brian; Wagner, Robert; Jackson, Roderick; Green, Johney
Graphical abstract: Highlights: Additive manufacturing plus hardware-in-the-loop speed up vehicle development process. Additive manufacturing shown to provide design flexibility and fast turnaround time. Powertrain integrated and optimized though HIL testing prior to vehicle installation. Printed electric vehicle experiments show range extension with natural-gas genset. Vehicle experiments confirm simulation + HIL + AM process to accelerate vehicle design. Abstract: Rapid vehicle and powertrain development has become essential to for the design and implementation of vehicles that meet and exceed the fuel efficiency, cost, and performance targets expected by today's consumer while keeping pace with reduced development cycle and more frequent product releases. Recently, advances in large-scale additive manufacturing have provided the means to bridge hardware-in-the-loop (HIL) experimentation and preproduction mule chassis evaluation. This paper details the accelerated development of a printed range-extended electric vehicle (REEV) by Oak Ridge National Laboratory, by paralleling hardware-in-the-loop development of the powertrain with rapid chassis prototyping using big area additive manufacturing (BAAM). BAAM's ability to accelerate the mule vehicle development from computer-aided design to vehicle build is explored. The use of a hardware-in-the-loop laboratory is described as it is applied to the design of a range-extended electric powertrain to be installed in a printed prototype vehicle. The integration of the powertrain and the opportunities and challenges it presents are described in this work. A comparison of offline simulation, HIL and chassis rolls results is presented to validate the development process. Chassis dynamometer results for battery electric and range extender operation are analyzed to show the benefits of the architecture.